Questioning Social Expectation towards Masculinity in Cloud 9 by Caryl Churchill - Khalilah Aisyah Maharani (Universitas Negeri Semarang, 2026)
This study examines the depiction of masculinity and its resistance in Caryl Churchill's play Cloud 9 (1979). Social expectations rooted in patriarchal culture enforce rigid standards of masculinity from childhood, suppressing authentic identities to maintain gender conformity. Therefore, this research aims to 1) To identify how the masculine actions in the play differ from the expectations of the Victorian period and 2) To explore how these